2021
DOI: 10.48550/arxiv.2101.08094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalized Turán problems for complete bipartite graphs

Dániel Gerbner,
Balázs Patkós

Abstract: For graph G, F and integer n, the generalized Tuán number ex(n, G, F ) denotes the maximum number of copies of G that an F -free n-vertex graph can have. We study this parameter when both G and F are complete bipartite graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Let us show a simpler example where ex na (n, H, F ) = ex(n, H, F ). Gerbner and Patkós [15] showed that if 2 < t < t ′ , then ex(n,…”
Section: Introductionmentioning
confidence: 99%
“…Let us show a simpler example where ex na (n, H, F ) = ex(n, H, F ). Gerbner and Patkós [15] showed that if 2 < t < t ′ , then ex(n,…”
Section: Introductionmentioning
confidence: 99%